The Implementation of the Jigsaw Learning Model to Improve Student Learning Outcomes in Basic Automotive Engineering (BAE) at SMKN 2 Serang City - Kurniawan, Taufik Indra; Iman , Atep; Abdillah, Hamid (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to evaluate the impact of implementing the Jigsaw cooperative learning model on student learning outcomes in Basic Automotive Engineering (BAE) at SMKN 2 Serang City. The research is motivated by the low student achievement, lack of motivation, and minimal active participation in learning, which has been conducted using the conventional lecture method. This research uses a quasi-experimental method with a non-equivalent control group design. The sample consists of two classes: the experimental class, which applies the Jigsaw model, and the control class, which uses a conventional learning approach. The instruments used were pre-test and post-test to measure cognitive learning outcomes. The analysis results show a significant difference between the learning outcomes of the experimental and control classes, as evidenced by the paired sample t-test with a significance value of 0.000 < 0.05. The average post-test score of the experimental class was 85.30, while the control class had a score of 74.29. These findings indicate that the Jigsaw learning model significantly improves student learning outcomes. Therefore, the Jigsaw model can be an alternative active learning method to enhance vocational education quality in the automotive field.